Kepemimpinan Kepala Desa Dalam MeningkatkanKesadaran Masyarakat Membayar Pajak Bumi DanBangunan - Rivica Mokodongan (Universitas Negeri Gorontalo, 2021)
The purpose of this study was to determine how much influence the village head's leadership had on public awareness in paying land and building taxes in Kinomaligan Village, Dumoga Tengah District, Bolaang Mongondow Regency. This study uses a quantitative approach with the method used is a correlational quantitative method with a sample of 55 people. Data collection techniques used in this study were interviews, questionnaires, documentation and data analysis techniques in this study using simple regression. The results showed that there was an influence of village head leadership on public awareness in paying land and building taxes in Kinomaligan Village, Dumoga Tengah District, Bolaang Mongondow Regency. The Great Influence of Village Head Leadership on Public Awareness of Paying Land and Building Taxes reached 42.8% while the remaining 47.2% was influenced by other variables such as public financial condition and public awareness of the importance of paying taxes.